Effect of some Vegetable Oils on Insect Infestation during Storage of Dry Cured Fish - Mathen, Cyriac; T.S., Unnikrishnan Nair; P., Ravindranathan Nair (Fishery Technology, 2025)
Twelve vegetable oils, viz., gingelly oil, sunflower oil, safflower oil, palm oil, rice bran oil, castor seed oil, mustard oil, groundnut oil, neem oil, hydnocarpus oil and cashewnut shell liquid were studied for their insect repellency in dry cured fish. Gingelly oil, mustard oil, sunflower oil,and hydnocarpus oil were found to posses insect repellancey whereas pahn oil attracted insects. Gingelly oil, mustard oil and sunflower oil delayed infestation with blowflies whereas hydnocarpus oil was good against both blowflies and beetles. It was observed that blowflies wereprevalent during rainyseason and beetles duringnon-rainy season. The preservative treatment for cured fish with a mixture of calcium propionate, butylated hydroxy anisole andchlorine was effective in delaying insect infestation in addition to preventing red